Exploring the job demands and support resources of Intensive Care Unit nurses in Cyprus' public hospitals - Despo Konstantinou; Eugenia Minasidou; Maria Grizioti; Charitini Tsagari; Thaleia Bellali (Ene, 2018)
Introduction: The nursing profession is characterized by high levels of job stress and burnout. Stress and burnout are experienced mostly by nurses working in departments that have to deal with acute events and incidents that often lead to death, as the department of Intensive Care Unit (ICU). Research is focusing to work stress factors that affect nursing staff. These factors are the environment and working conditions, the individual characteristics of each nurse and the contact with patients and relatives. Purpose: The purpose of this study is to investigate the working conditions under which nursing staff offer their services at the Intensive Care Unit (ICU) and to highlight those factors that impede or facilitate their work. Methods: The study involved a cross-sectional descriptive type of research. The sample consisted of 155 ICU nursing staff of public hospitals in Cyprus. Data were collected through a questionnaire which included the following tools: a questionnaire recording job demands and sources of support (Job Demands and Resources) and the Maslach Burnout Inventory. For the statistical analysis and data processing, the statistical analysis package for Social Sciences was used (Statistical Package for Social Sciences, SPSS) version 20. Results: The majority of the sample was women (72.3%) with a mean age of 35.5 years. For the three dimensions of MBI, results showed that the majority of nursing staff (42.7%) had low emotional exhaustion, all the nursing staff who responded lacked of personal accomplishments, while the majority (38%) showing high levels of impersonal care. It was shown that the job requirements provided emotional exhaustion (p< 0.05), while the working funds did not provide impersonal care (p> 0.05). The correlations between job demands and job resources showed a statistically significant relationship between age, total years of service and years of experience in hospital nursing departments with respect and support factors (r =- 0.24, p = 0.002, r =- 0.26, p =0.001, r=-o.28, p<0.001) and autonomy and control (r=-0.19, p=0.0014, r=-0.17, p=0.034, r=-0.17, p=0.0035), respectively. Conclusions: Burnout of ICU nurses in Cyprus public hospitals was found to be of medium levels and was confirmed that several working, personal and social factors might contribute to the phenomenon. Early recognition and taking immediate measures for prevention are more than necessary.